Implementação do lean em instituições de ensino superior públicas: revisão de literatura e proposição de melhoria de processos - Rodrigues, Marcelo Sales (Universidade Federal de São Carlos, 2025)
Lean is a methodology that aims to eliminate waste, improve organizational performance, and increase customer satisfaction. This approach has been used in various types of public and private organizations, including Higher Education Institutions (HEIs). The application of Lean principles, tools, and practices in these organizations can bring significant benefits to public HEIs, as these organizations face budget constraints and challenges in efficiently managing processes. However, it is important to understand how Lean can be implemented and the challenges involved in its implementation in public HEIs. Therefore, the main objective of this study was to analyze the literature on Lean implementation in public HEIs, associating the findings with process improvement proposals. Using a multimethod approach, this dissertation consists of two articles. The first article aimed to conduct a Systematic Literature Review (SLR) on the implementation of Lean in public HEIs to identify applications, barriers, and benefits achieved. Searches were conducted in two databases, Scopus and Web of Science. After applying inclusion and exclusion criteria, 21 articles were selected for bibliometric and thematic analysis. The results highlight that among the main barriers identified are the lack of involvement from leadership and public servants, as well as the lack of communication between different sectors of HEIs. Among the benefits are waste elimination, cost reduction, performance improvement, and increased customer satisfaction. The observed results allow for an analysis of the literature in the field and provide HEI managers with information to improve performance by applying Lean principles. The second article analyzed the application of Lean in the Transportation Sector at the Sinop University Campus (CUS/UFMT), where wastes affecting efficiency were identified. Tools such as Value Stream Mapping (VSM) and the 5W1H plan were used to propose improvements that eliminate redundancies and streamline processes. The proposals include document digitization, improving communication in transportation requests, and separating simple and complex maintenance, with specialized technical diagnoses for the latter. These initiatives aim to reduce time and costs, increase efficiency, and optimize resource use. The implementation requires a detailed plan and training, ensuring the consolidation of a continuous improvement culture. The study demonstrates the potential of Lean philosophy to improve the quality and efficiency of services in public HEIs.
Lean implementation in public higher education institutions: literature review and proposal for process improvement
Keywords: Lean; Instituição de ensino superior; Serviço público; Ferramentas lean; Setor de transporte; Higher education institution; Public service; Lean tools; Transportation sector; ENGENHARIAS::ENGENHARIA DE PRODUCAO::ENGENHARIA DO PRODUTO::PROCESSOS DE TRABALHO